Introduction - Mervi Rajahonka; Dorota Kwiatkowska-Ciotucha; Miet Timmers; Urszula Załuska; Kaija Villman (Emerald Publishing Limited, 2022)
People with a dual care task at home, taking care of a younger and an older generation family member, are often called the sandwich generation (SG). They are more often women than men, at high risk of burnout or withdrawal from the labour market. This book provides international comparisons and offers tools for working sandwich generation (WSG) women and their supervisors for managing challenging situations in working life. The book is multidisciplinary and combines theories with qualitative and quantitative empirical research, practical tools and case studies. This chapter introduces the themes and relevant concepts of the book and presents its structure.
10.1108/978-1-80262-501-120221001; 10.1108/978-1-80262-501-120221001; Working Women in the Sandwich Generation: Theories, Tools and Recommendations for Supporting Women's Working Lives; EBP077208358